The study of UCH-L1 and S100B serum concentration in the diagnosis of diffuse and focal severe traumatic brain injury - Oleg Y. Kobyletsky; Lyudmyla M. Bielska; Volodymyr M. Shevaha; Vadym V. Biloshytsky (Ukrainian Neurosurgical Journal, 2017)
Purpose: To evaluate the feasibility of determining serum concentration of biomarker of neuronal protein damage UCH-L1 and biomarker of astroglia damage S100 on the 1st day after injury, particularly for the diagnosis of focal and diffuse brain impairments based on clinical and biochemical and computer tomographic study in patients with acute severe brain injury.Methods. We used the results of diagnostic tests and therapeutic manipulations in 72 patients aged 16 to 76 years with severe traumatic brain injury. Correlation of the molecular biological study results (determining the UCH-L1 and S100B serum concentration by solid phase enzyme immunoassay — ELISA using sets of reagents Sigma-Aldrich, USA, on the 1st day after severe TBI) with the injury type (diffuse or focal according to L. F. Marshall classification) was evaluated.Results. In patients with isolated severe TBI, after exclusion of concomitant extracranial injuries, intoxication and other causes for unconsciousness, UCH-L1 / S100B concentration ratio exceeding the cut-off value of 15.8 indicated a high probability of diffuse injury, ratio less than 15.8 was a marker of focal injury. The sensitivity of the model was 77.8%, specificity — 79.6%.Conclusion. It has been shown that the estimation of serum concentration of neuronal damage biomarker UCH-L1 and astroglial damage biomarker S100B in patients with severe TBI on the 1st day after injury allows diagnose diffuse and focal brain damage with high efficiency.